2021
DOI: 10.1016/j.scog.2020.100193
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE E2 and low-density lipoprotein with depressive symptoms in Chinese senile schizophrenia inpatients: A cross-sectional study

Abstract: Background Schizophrenia is considered to occur due to both environmental and genetic factors. Depressive symptoms and apolipoprotein E ( APOE ) gene polymorphisms are involved in the pathogenesis of schizophrenia. However, the effect of APOE gene polymorphism on depressive symptoms has never been investigated among Chinese elderly schizophrenia patients. Objective This cross-sectional study aimed to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The human apolipoprotein E (ApoE) variant originates from two functional polymorphisms (rs429358 and rs7412) in exon 4 of the ApoE gene, which can be combined to form three major subtypes (2,3 and 4) [15]. Previous studies have shown that ApoE gene polymorphism may affect the level of lipoprotein [16][17][18] and also affect the development of schizophrenia [19,20]. For example, one study found a significant association between ApoE 3 gene variation and schizophrenia in Asian populations [19]; Another study found a significant association between ApoE rs429358 or ApoE rs7412 polymorphisms and low-density lipoprotein levels (LDL) in whites and African Americans [21].…”
Section: Introductionmentioning
confidence: 99%
“…The human apolipoprotein E (ApoE) variant originates from two functional polymorphisms (rs429358 and rs7412) in exon 4 of the ApoE gene, which can be combined to form three major subtypes (2,3 and 4) [15]. Previous studies have shown that ApoE gene polymorphism may affect the level of lipoprotein [16][17][18] and also affect the development of schizophrenia [19,20]. For example, one study found a significant association between ApoE 3 gene variation and schizophrenia in Asian populations [19]; Another study found a significant association between ApoE rs429358 or ApoE rs7412 polymorphisms and low-density lipoprotein levels (LDL) in whites and African Americans [21].…”
Section: Introductionmentioning
confidence: 99%
“…After the full‐text analysis, 70 studies were further excluded and two studies retrieved from reviews were further added. As shown in Figure 2, 46 studies conducted in different countries were included in the final review, including the USA, Spain, Iran, China, Korea, Brazil, Italy, Sweden, Australia and Chile (Alhareeri et al., 2020; Bai et al., 2017; Buchhave et al., 2012; Cheng et al., 2017; de Sousa et al., 2020; Estévez‐López et al., 2018, 2021a, 2021b; Feng et al., 2018; Finegold et al., 2012; Fourie et al., 2014; Fu et al., 2016, 2021; Gaitán et al., 2021; Gamarra et al., 2015; Gill et al., 2015; Gonzalez et al., 2018; Henderson et al., 2017; Herrada et al., 2020; Hsiao et al., 2013, 2016; Kim et al., 2013, 2019; Kober et al., 2016; Lanni et al., 2012; Leung et al., 2014; Li, 2020; Li et al., 2019; Lukkahatai et al., 2014; Luo et al., 2021; Maffioletti et al., 2016; Miaskowski et al., 2013; Newman et al., 2012; Peña‐Zarza et al., 2018; Pierzynski et al., 2018; Pressler et al., 2015; Rausch et al., 2012; Seyedmirzaee et al., 2016; Sloan et al., 2012; Sun et al., 2020; Tao et al., 2016; Wang et al., 2014, 2021; Xu et al., 2018; Yang et al., 2020; Zhang et al., 2020). As shown in Table 1, only two studies (4.35%) mentioned the precision in measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies suggested that lifestyle or diet habits, such as sleep duration, and the intakes of n‐3 fatty acids, n‐6 fatty acid, and fiber, were associated with anxiety or depression (de Sousa et al., 2020; Xu et al., 2018; Zhang et al., 2020). Four studies provided information on precision in the characterization of biomarkers (Cheng et al., 2017; Kim et al., 2013; Li 2020; Maffioletti et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that the frequency of the ε4 allele was significantly higher in schizophrenia patients with positive symptoms [ 64 ]. A study also found that ApoE ε2 genotype was associated with more depressive symptoms in older Chinese schizophrenia patients[ 65 ]. One possible reason for this is that the combined effect of rs429358 and rs7412, but not rs429358 alone, has a significant effect on the PANSS score of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%